The Endless Reconstruction and Modern Disasters The Management of Urban Space Through an Earthquake - Messina, 1908-2018 - Farinella, Domenica; Saitta, Pietro (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines the long-lasting consequences of the Messina earthquake, a disaster that struck the city of Messina, Sicily, in 1908. The quake killed 86,000 people and destroyed one of the most important port cities in the Mediterranean. The authors argue that contemporary notions of "disaster economy" and "shock economy" are not specifically features of the present. On the contrary, the elements that characterize contemporary disaster-related speculative processes were largely active at the very beginning of the past century and helped the formation of the present. In addition to considering the historical significance of the earthquake, the authors pay particular attention to the impact of the earthquake on the structural victims of this enduring disaster: the members of the marginal class of people that emerged from the reconstruction. Through the biographical analysis of the inhabitants of shacks and projects, the study analyzes the intergenerational continuity of thesubaltern urban experience. Domenica Farinella, PhD, is a Lecturer in Economic Sociology at the University of Messina, Italy. Pietro Saitta, PhD, is a Senior Lecturer in Sociology at the University of Messina, Italy.